Angelica sinensis (Umbelliferae) with proven repellent properties against Aedes aegypti, the primary dengue fever vector in Thailand - D. Champakaew (2018)
© 2015, Springer-Verlag Berlin Heidelberg. Botanical resources with great diversity in medicinal and aromatic plants are a rich and reliable source for finding insect repellents of plant origin, which are widely popular among today’s consumers. Although some herbal-based repellents have been proven comparable to or even better than synthetics, commercially available natural repellents generally tend to be expensive, with short-lived effectiveness. This critical flaw leads to ongoing research for new and effective repellents, which provide longer protection against vector and nuisance-biting insects, while remaining safe, user friendly, and reasonably priced. This study aimed to evaluate the repellent activity of plant-derived products against the primary dengue vector, Aedes aegypti, by following the human bait technique of World Health Organization guidelines. Preliminary laboratory screening tests for repellency of 33 plant species clearly demonstrated Angelica sinensis as the most effective repellent from each kind of extracted product, with its essential oil and ethanolic extract having median complete protection times of 7.0 h (6.0–7.5) and 2.5 h (2.0–2.5), respectively. Due to its low yield (0.02 %), pungent smell, and little cause of irritation, A. sinensis essential oil did not qualify as a candidate for further repellent assessment. However, subsequent extractions of A. sinensis with different organic solvents of increasing polarity provided four extractants with varying degrees of repellency against A. aegypti. The hexane extract of A. sinensis provided excellent repellency, with a median complete protection time of 7.5 h (6.5–8.5), which was longer than that of ethanol (2.5, 2.0–2.5 h), acetone (1.75, 0.5–2.5 h), and methanol extracts (0.5, 0–1.0 h). By being the most effective product, A. sinensis hexane extract gave significant protection comparable to that of its essential oil and the standard synthetic repellent, N,N-diethyl-3-methylbenzamide (DEET: 6.25, 5.0–6.5 h). Qualitative gas chromatography/mass spectrometry analysis demonstrated the presence of phthalides and phthalates, including 3-N-butylphthalide, butylidenephthalide, ligustilide, and di-iso-octyl phthalate, as the principal constituents in A. sinensis products. The success of A. sinensis products, particularly that of hexane extract, has proved their potential as bioactive candidates in the next step for developing and producing alternative natural repellents with commercial aspirations.